Tantangan Kompetensi SDM dalam Menghadapi Era Digital: Sebuah Literatur Review - Ahmad Naffis Ayyasy; Shintya Maelani (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This article discusses the challenges of human resource (HR) competencies in the digital era, organizational strategies to enhance these competencies, and the roles of governments and educational institutions. The digital era demands HR to adapt to technological advancements and manage changes swiftly. Organizations need to provide training, continuous development, and create a work climate that fosters innovation. Meanwhile, governments and educational institutions play crucial roles in establishing ecosystems that support HR competency improvement. This research is supported by a literature analysis of 10 relevant scientific articles. The article also offers implementation strategy recommendations based on recent research findings.